RNase-like domain in DNA-directed RNA polymerase II. - Shirai, T (1991)
DNA-directed RNA polymerase is responsible for gene expression. Despite its importance, many details of its function and higher-order structure still remain unknown. We report here a local sequence similarity between the second largest subunit of RNA polymerase II and bacterial RNases Ba (barnase), Bi, and St. The most remarkable similarity is that the catalytic sites of the RNases are shared with the eukaryotic RNA polymerase II subunits of Drosophila melanogaster and Saccharomyces cerevisiae. Several amino acids conserved among the RNases and the RNase-like domains of the RNA polymerase subunits are located in the neighborhood of the catalytic sites of barnase, whose three-dimensional structure has been resolved. This observation suggests the functional importance of the RNase-like domain of the RNA polymerase subunits and indicates that the RNase-like domain may have RNase activity. The location of the RNase-like domain relative to the region necessary for RNA polymerization is similar to the relative proximity of 5'----3' or 3'----5' exonuclease and the region of polymerase activity of DNA polymerase I. The RNase-like domain might work in proofreading, as in RNA-directed RNA polymerase of influenza virus, or it may contribute to RNA binding through an unknown function.